THE ANTICIPATION STRATEGY OF BEIRUT BOMB RELATED TO IRREGULAR WARFARE FOR INDONESIA IN THE FUTURE - Renny Setiowati; Pujo Widodo; Resmanto Widodo Putro (JOURNAL ASRO, 2020)
ABSTRACT This irregular phenomenon which later gave rise to the term irregular warfare. The phenomenon of threats at the global level has also increased in volume. The Beirut bombing in Lebanon occurred Just before 6 pm, reports of Beirut time began flooding into Twitter about the fires and the series of explosions in Beirut. It quickly became evident that it was much more than just a small industrial fire. Before long, videos and images of the massive explosion flooded social media. The video below is a real-life example, showing a fire suddenly turning into a huge fireball and the shockwave tearing apart a building. The Beirut bombing in Lebanon The Indonesian government needs to issue a new policy regarding the raising of reserve components and support that needs to be prepared early through education and training which is then disseminated into the community to mingle and become an espionage agent to anticipate irregular warfare, Nationalism education that emphasizes pride in potential a nation, which does not have to be measured in terms of other nations, needs to be developed to anticipate the global era and cosmopolitanism. Keywords: Bomb Beirut, irregular warfare.